Analisis Risiko Menggunakan Metode House of Risk (HOR) pada Peternakan Sapi Perah Rembangan Dairy Farm Kabupaten Jember - Cindy Padma Widhah; Intan Kartika Setyawati; Joni Murti Mulyo Aji; Cindera Rosa Damascena; Illia Seldon Magfiroh (Jurusan Sosial Ekonomi, Fakultas Pertanian, Universitas Andalas, 2025)
Dairy farming is one of the agribusiness sectors that is highly vulnerable to various risk threeats, ranging from feed price fluctuations to disease risks and livestock deaths. Risk analysis in dairy farming is a systematic process which aims to identify and manage potential risks or uncertainties that can negatively affect dairy cattle farming businesses. The method used in this research is descriptive quantitative with a House of Risk (HOR) approach. The location of this research is at the Rembangan Dairy Farm in Kemuning Lor village, Arjasa sub-district. The objective of this study is to determine the priority risk agents and preventive actions at Rembangan Dairy Farm. The results show there are two priority risk agents: dairy cattle diseases (A7) and insufficient number of lactating cows (A9), with one priority preventive action being the administration of medicine and vitamins (PA2).